Muscling selection in swine and its effect on carcass traits - J D Wheat; Donald H Kropf; C H Chang; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1973)
Pigs farrowed in May, 1972, were the first born in the select and control lines. Performances of animals in the two lines were essentially the same. However, ham firmness and color differed significantly (P<0.0l) between lines, with those in the select line firmer and darker than those from the control line.; Swine Day, Manhattan, KS, November, 1973
Keywords: Swine day; 1973; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 203; Swine; Muscling; Carcass traits; Performance; Ham firmness; Ham color